Photochemistry in the arctic free troposphere: NOx budget and the role of odd nitrogen reservoir recycling - Stroud, Craig; Madronich, Sasha; Atlas, Elliot; Ridley, Brian; Flocke, Frank; Weinheimer, Andy; Talbot, Bob; Fried, Alan; Wert, Brian; Shetter, Richard; Lefer, Barry; Coffey, Mike; et al. (Atmospheric Environment, 2003)
The budget of nitrogen oxides (NOx) in the arctic free troposphere is calculated with a constrained photochemical box model using aircraft observations from the Tropospheric O3 Production about the Spring Equinox (TOPSE) campaign between February and May. Peroxyacetic nitric anhydride (PAN) was observed to be the dominant odd nitrogen species (NOy) in the arctic free troposphere and showed a pronounced seasonal increase in mixing ratio. When constrained to observed acetaldehyde (CH3CHO) mixing ratios, the box model calculates unrealistically large net NOx losses due to PAN formation (62pptv/day for May, 1-3km). Thus, given our current understanding of atmospheric chemistry, these results cast doubt on the robustness of the CH3CHO observations during TOPSE. When CH3CHO was calculated to steady state in the box model, the net NOx loss to PAN was of comparable magnitude to the net NOx loss to HNO3 (NO2 reaction with OH) for spring conditions. During the winter, net NOx loss due to N2O5 hydrolysis dominates other NOx loss processes and is near saturation with respect to further increases in aerosol surface area concentration. NOx loss due to N2O5 hydrolysis is sensitive to latitude and month due to changes in diurnal photolysis (sharp day-night transitions in winter to continuous sun in spring for the arctic). Near NOx sources, HNO4 is a net sink for NOx; however, for more aged air masses HNO4 is a net source for NOx, largely countering the NOx loss to PAN, N2O5 and HNO3. Overall, HNO4 chemistry impacts the timing of NOx decay and O3 production; however, the cumulative impact on O3 and NOx mixing ratios after a 20-day trajectory is minimal. © 2003 Elsevier Science Ltd. All rights reserved.